MODERN PROCESS AUTOMATION SYSTEM FOR MELTING STEEL IN INDUCTION FURNACES AND ELECTRIC ARC FURNACES - A. G. Mizgir; R. E. Aladjev (Литьë и металлургия)
The exumple of the modern control system of melting pricess in are strrl-smelting furnace is given.